Value of Humanized Nursing under Emergency Green Channel on Gastrointestinal Function Recovery in Patients with Acute Intestinal Obstruction after Operation - Siqi Luo; Yan Wang (Emergency Medicine International)
Acute intestinal obstruction (AIO) is one of the most common surgical acute abdomens. Emergency green channel refers to a fast and efficient service system provided by hospitals for critically ill patients. It is the key to ensure that emergency patients receive timely, standardized, efficient and thoughtful medical services, improve the success rate of rescue, and reduce medical risks. Acute intestinal obstruction is mainly treated by surgery in the clinic. Previous reports have shown that the application of different nursing methods in the operation of acute intestinal obstruction has different effects on the results of surgical treatment. In this study, the clinical data of 80 patients with AIO were retrospectively analyzed to explore the value of humanistic care under the emergency green channel in promoting the recovery of gastrointestinal function after AIO surgery.